Application of performance based nonlinear static pushover analysis for seismic design of RC buildings - Bhatti, A. Q. (2013)
Seismic retrofitting of already constructed buildings is one of the most effective methods of decreasing the risk. However the seismic performance of the structure may not be improved by Strengthening unless the professional engineer selects an appropriate modifying technique based on seismic evaluation of the already constructed structures. In this paper nonlinear static pushover analysis has been performed for the said building. The demand spectrum of ATC 40 procedure for this building was compared with real site based demand spectra. The simulation has been compared with and without strengthened structure. The plastic hinges of the building have been plotted for different safety margins.